2013
DOI: 10.1200/jco.2013.31.6_suppl.72
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric antigen receptor (CAR+) modified T cells targeting prostate-specific membrane antigen (PSMA) in patients (pts) with castrate metastatic prostate cancer (CMPC).

Abstract: 72 Background: A phase I dose-escalating study to assess safety, dose and targeting efficiency of genetically modified autologous human T cells targeted to PSMA was initiated. Preclinical models demonstrated anti-tumor activity and accumulation, migration, and persistence of these cells to tumor. The autologous PSMA-targeted T cells utilizes the P28z second generation chimeric antigen receptor following iv cyclophosphamide (Cy). For safety, the herpes simplex virus-1 thymidine kinase (hsvtk) gene is co-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 0 publications
0
42
0
1
Order By: Relevance
“…Generation of isogenic cell lines from parental U87 cells (here referred to as WT) bearing dCK, dCK-R104M/D133A (dCKDM) [9, 10], dCK-R104Q/D133N (dCKep16A) [11], dCK-A100V/R104M/D133A (dCK3M) [10, 11], TK2-N93D/L109F (TK2DM) [14], and HSVTK reporter genes fused to the green fluorescent protein (GFP) were described previously [15]. SFG-based helper-free retroviruses encoding each of the mutant genes were produced by transient transfection of H29 producer cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of isogenic cell lines from parental U87 cells (here referred to as WT) bearing dCK, dCK-R104M/D133A (dCKDM) [9, 10], dCK-R104Q/D133N (dCKep16A) [11], dCK-A100V/R104M/D133A (dCK3M) [10, 11], TK2-N93D/L109F (TK2DM) [14], and HSVTK reporter genes fused to the green fluorescent protein (GFP) were described previously [15]. SFG-based helper-free retroviruses encoding each of the mutant genes were produced by transient transfection of H29 producer cells.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, HSVTK with the F-18 radiolabeled 9-[4-[ 18 F]fluoro-3-(hydroxymethyl)butyl]guanine ([ 18 F]FHBG) detected localization of adoptively transferred cytotoxic T lymphocytes in a glioma patient [8]. Ongoing clinical trials at Memorial Sloan Kettering Cancer Center and other institutes further support reporter gene imaging as a promising technology for monitoring gene and cell-based therapies [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Besides the aforementioned phase I trial in patients with castrate-resistant prostate cancer (NCT01140373), there is only 1 other trial in patients with advanced castrate resistant prostate cancer after non-myeloablative conditioning (NCT00664196) [63]. There is rationale for combining CAR T cell therapy with checkpoint blockade, AR-direceted therapy or cytotoxic chemotherapy in an effort to augment CAR T cell efficacy, decrease tumor burden or facilitate antigen spreading.…”
Section: Car T Therapymentioning
confidence: 99%
“…Several trials investigating CAR T-cell therapy in solid tumors have been initiated, but efficacy has been low. Best responses recently reported in trials using CAR T cells specific for the solid tumor antigens mesothelin, PSMA, or ERBB2 were stable disease in 24-67% of patients (42-44). The efficacy of CAR T-cell therapy in solid tumors may be reduced due to several factors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, both PSCA and PSMA were targeted in a preclinical study that showed that CAR T cells can be engineered to recognize only tumors expressing both antigens, thereby increasing CAR T-cell specificity and reducing off-tumor effects (40). A phase 1 clinical trial (NCT01140373) using PSMA-specific CAR T cells in patients with metastatic prostate cancer resulted in stable disease in 2 of 4 patients treated (44). …”
Section: Introductionmentioning
confidence: 99%